Fatty liver oxidative events monitored by autofluorescence optical diagnosis: Comparison between subnormothermic machine perfusion and conventional cold storage preservation. Issue 7 (15th September 2016) - Croce, Anna Cleta; Ferrigno, Andrea; Bertone, Vittorio; Piccolini, Valeria Maria; Berardo, Clarissa; Di Pasqua, Laura Giuseppina; Rizzo, Vittoria; Bottiroli, Giovanni; Vairetti, Mariapia
Aim: Aims: Livers with moderate steatosis are currently recruited as marginal organs to face donor shortage in transplantation, even though lipid excess and oxidative stress increase preservation injury risk. Sensitive, real‐time detection of liver metabolism engagement could help donor selection and preservation procedures, ameliorating the graft outcome. Hence, we investigated endogenous biomolecules with autofluorescence (AF) properties as biomarkers supporting the detection of liver oxidative events and the assessment of metabolic responses to external stimuli. Methods: Livers from male Wistar rats fed a 12‐day methionine/choline‐deficient (MCD) diet were subjected to AF spectrofluorometric analysis (fiber‐optic probe, 366‐nm excitation) before and after organ isolation, and following preservation (cold storage or 20°C machine perfusion) and reperfusion. Results: Innovative dynamic AF results on lipid oxidation to lipofuscin‐like lipopigments, correlating with biochemical oxidative damage (thiobarbituric acid reactive substances) and antioxidant defense (glutathione) parameters, suggested lipid engagement in MCD livers counteracting reactive oxidizing species. The maintained MCD liver functionality was supported by limited changes in bilirubin AF spectral profile, reflecting bile composition balance, despite their intrinsic mitochondrial weakness, confirmed by adenosine 5′‐triphosphate levels, and regardless of different preservation effects on energy metabolism revealed by conventional reduced forms of nicotinamide adenine dinucleotide and nicotinamide adenine dinucleotide phosphate and flavin AF data. Conclusion: Autofluorescence showed that, after a relatively short time on an MCD diet, livers are still able to face oxidizing events and maintain a functional balance. These results strengthen AF as a supportive diagnostic tool in experimental hepatology, to characterize marginal livers in real time, monitor their response to ischemia/reperfusion, and investigate protective therapeutic agents.